2018
DOI: 10.1007/s11067-018-9425-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Daily Urban Systems: A Heterogeneous Commuting Network Approach

Abstract: Daily Urban Systems (DUSs) are not only an attractive concept for planning locations for jobs, housing, schools and retail, but also for managing services such as public transportation and health care. If we can match geographically demand and supply of goods and services, higher levels of spatial efficiency can be reached. Since 50 years most of the research delineating DUSs uses thresholds of commuting levels, thus identifying labor markets polarized towards central cities. Few research grasps the more recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Last but not least, although most people move regularly, different demographic groups may have different movement behaviors. For example, the movements of women are usually shorter than those of men ( Verhetsel, Beckers, & De Meyere, 2018 ), and low-income people seldom engage in long-distance travel due to the unaffordability of travel fees or costs ( Casado-Díaz, 2000 ). Previous studies have shown that different social-demographic groups have functional regions of different sizes ( Farmer & Fotheringham, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, although most people move regularly, different demographic groups may have different movement behaviors. For example, the movements of women are usually shorter than those of men ( Verhetsel, Beckers, & De Meyere, 2018 ), and low-income people seldom engage in long-distance travel due to the unaffordability of travel fees or costs ( Casado-Díaz, 2000 ). Previous studies have shown that different social-demographic groups have functional regions of different sizes ( Farmer & Fotheringham, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…These stabilisations are then represented as regions within which interactions are most cohesive (e.g. Verhetsel et al 2018). However, this method makes it difficult to establish causes of this cohesiveness.…”
Section: Methodsmentioning
confidence: 99%
“…La forte dispersion en Belgique de la population et de l'emploi explique ces chiffres. Pour obtenir une délimitation des zones complexes des mouvements pendulaires, une autre approche est nécessaire : non une orientation vers une agglomération centrale mais une analyse de réseaux (Verhetsel et al, 2018).…”
Section: La Ville Centraleunclassified